Sexuality and the rise of China : the post-1990s gay generation in Hong Kong, Taiwan, and mainland China - Kong, Travis (Duke University Press, 2023)
"In Sexuality and the Rise of China Travis S. K. Kong examines the changing meanings of same-sex identities, communities, and cultures for young Chinese gay men in contemporary Hong Kong, Taiwan, and mainland China. Drawing on ninety life stories, Kong's transnational queer sociological approach shows the complex interplay between personal biography and the dramatically changing social institutions in these three societies. Kong conceptualizes coming out as relational politics and the queer/tongzhi community and commons as an affective, imaginative means of connecting, governed by homonormative masculinity. He shows how monogamy is a form of cruel optimism and envisions state and sexuality intertwining in different versions of homonationalism in each location. Tracing the alternately diverging and converging paths of being young, "Chinese," gay, and male, Kong reveals how both Western and emerging inter-/intra- Asian queer cultures shape queer/tongzhi experiences. Most significantly, at this historical juncture characterized by the rise of China, Kong criticizes the globalization of sexuality by emphasizing inter-Asia modeling, referencing, and solidarities and debunks the essentializing myth of Chineseness, thereby decolonizing Western sexual knowledge and demonstrating the differential meanings of Chineseness/queerness across the Sinophone world"--